Swirling Airflow Influence on Turbocharger Compressor Performance - Peciura, Justinas (My University, 2015)
Master Thesis work was done at Volvo Cars, Powertrain Installation department, Air Induction System group. Scope of the thesis was to investigate clean side duct and optimize it for compressor performance. After literature review work was narrowed down and focused on swirling airflow and its influence on turbocharger compressor performance from efficiency and NVH point of view. Throughout thesis work CFD simulations were used to design swirl generators and investigate swirl behaviour in the ducts. Then, flow bench experimental tests were done to validate CFD simulations and define best settings for swirl modelling. Finally, experimental tests were done in turbocharger test rig to investigate swirl influence on compressor performance. Thesis outcome was a set of guidelines for Air Induction System group, that covers swirl creation methods and swirl effect on compressor performance. Results showed that swirling motion can move compressor map improving surge or choke limit. In addition, small amounts of positive swirl can also improve compressor efficiency up to 0.8%.
Keywords: Farkostteknik; Hållbar utveckling; Strömningsmekanik och akustik; Transport; Vehicle Engineering; Sustainable Development; Fluid Mechanics and Acoustics; Transport